Peran sentinel node pada kanker ginekologi - Fitriyadi Kusuma; Marshaly Safira Masrie; Geraldus Sigap Gung Binathara; Abdul Hafiidh Surya Putra; Kemal Akbar Suryoadji (Journal of Health and Therapy, 2026)
This review evaluated the role of sentinel lymph node mapping in early-stage gynecologic cancers, cervical, endometrial, and vulvar, as a staging approach that balanced diagnostic accuracy and patient safety. The search methods assembled evidence from major clinical trials and cohort studies on detection performance, diagnostic accuracy, and surgical morbidity compared with systematic lymphadenectomy. The findings indicated that this mapping achieved high detection rates with adequate sensitivity and reduced operative time, blood loss, and risks of lymphedema, lymphocele, and neurovascular injury. In cervical and endometrial cancer, multicenter and prospective studies demonstrated comparable oncologic safety alongside lower postoperative complications, whereas in vulvar cancer, a strategy based on a negative sentinel node reduced groin morbidity without compromising disease control in selected lesions. Tracer approaches, including radioisotopes, blue dye, and indocyanine green fluorescence, together with enhanced assessment through in-depth histopathology, supported broad clinical adoption. Overall, this review concluded that sentinel lymph node mapping was appropriate for routine use in suitable cases, provided bilateral mapping and standardized pathological evaluation.